Upaya Meningkatkan Hasil Belajar Siswa Melalui Strategi Pembelajaran Permainan Angka Tertempel di SD Inpres 3 Tolai - I Wayan Suada (Jurnal Paedagogy, 2021)
The purpose of this study was to improve student learning outcomes about mixed arithmetic in the Mathematics learning process using learning strategies through sticky numbers games. This study uses a classroom action research method which is carried out in 2 (two) cycles. Each cycle is carried out in 4 (four) stages, namely planning, acting, observing, and reflecting. The subjects of this study were Grade VI students of SD Inpres 3 Tolai in the 2020/2021 school year. Data collection techniques using tests, observation, and documentation. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. Based on the results of this study, it is known that the increase in student activity, the pre-cycle average is 49.68. In the first cycle it increased to 67.31, and the second cycle increased to 83.97. While the increase in student learning outcomes that have met the completeness value, namely pre-cycle by 50%. In the first cycle it increased, namely to be 79.17% and increased again in the second cycle to 100%.